The Hot Foot Syndrome: Evans’ Sign and the Old Way - RJ Evans; C Peter N Watson (Pain Research and Management)
BACKGROUND: Pelvic cancers such as cancer of the cervix can spread locally to involve adjacent structures such as the lumbosacral plexus and the sympathetic chain. When this happens the prognosis is usually poor. An early suspicion of recurrence may result in investigation leading to earlier and better treatment. A physical sign that may be an early and only sign of recurrence is described.